Paranoid Schizophrenia Suffered by the Lead Character on Kotoko Movie by Shinya Tsukamoto - Dwi Cahyo Arif Wibowo (Japanese Research on Linguistics, Literature, and Culture, 2019)
In this research, the writer explains about paranoid schizophrenia suffered by Kotoko. The purpose of this research is to analyze the characteristics and symptoms of paranoid schizophrenia. The data were taken from Kotoko movie created by Shinya Tsukamoto (2011). The method used to analyzed the data is descriptive qualitative. Within modern social society, schizophrenia is a kind of social phenomenon problem. The symptom that usually appear in paranoid schizophrenia is delusions and hallutinations. The results show that becoming a single mother, post traumatic stress, over protective individual trigger the paranoid schizophrenia.